2000
DOI: 10.1046/j.1365-2516.2000.00412.x
|View full text |Cite
|
Sign up to set email alerts
|

Immune tolerance for haemophilia patients with inhibitors: analysis of the western United States experience

Abstract: The experience with immune tolerance (IT) induction therapy for haemophilia patients with inhibitors, instituted during 1990-97 at 17 haemophilia treatment centres in the western United States, was reviewed. IT was instituted in 104 of 139 (75%) of all identified haemophilia A and haemophilia B patients with inhibitors. Doses and schedules for IT varied but most patients were treated with a daily administration of 25-200 units kg-1 day-1. Successful immune tolerance (defined as Bethesda Unit titres < 1.0) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Forty‐eight studies reported between 1982 and 2003 with 2704 patients receiving a total of 2973 CVADs were included in the meta‐analysis (Table 1) [2–4,6,7,9–22,27–55]. None of the studies was unpublished.…”
Section: Resultsmentioning
confidence: 99%
“…Forty‐eight studies reported between 1982 and 2003 with 2704 patients receiving a total of 2973 CVADs were included in the meta‐analysis (Table 1) [2–4,6,7,9–22,27–55]. None of the studies was unpublished.…”
Section: Resultsmentioning
confidence: 99%
“…One report of a survey of numerous centres in the western US [31] was excluded as it was not possible to separate out the results for patients with haemophilia A from those with haemophilia B.…”
Section: Populations Studiedmentioning
confidence: 99%
“…In numerous studies, an inhibitor titre below 10 BU mL )1 at the start of ITI has been found to correlate with improved outcomes [5,25,[28][29][30]. Based on these findings, published guidelines often suggest delaying ITI until the inhibitor titre has fallen to <10 BU mL )1 [31][32][33][34].…”
Section: Risk Factors For Unsuccessful Itimentioning
confidence: 99%